Sonic Stagings of U.S. Postwar Audiopoetry : Practices, Configurations, and Contexts of Poetry on Sound Carriers (c. 1950s-1980s) - Stackmann, Ulla, (DQR Studies in Literature ;, 2025)
As the first study of its kind, this book explores the publication of poetry on sound carriers in the US postwar era from an aesthetic as well as an historical point of view. Combining approaches from media and literary studies, it explains why labels and individuals like Amiri Baraka, Bernadette Mayer, or John Giorno straddled the lines between music, poetry, and visual arts using audio recording and playing devices. It sheds light on the sonic imaginaries that commercial and avant-gardist recording projects sought to mobilize and sometimes also unwittingly reproduced in this context.